Long-term outcome of endocardial-only versus combined endocardial-epicardial homogenization of the scar for treatment of ventricular tachycardia in patients with ischemic cardiomyopathy. (14th October 2021) - Mohanty, S; Trivedi, C; Della Rocca, D G; Gianni, C; MacDonald, B; Mayedo, A; Bassiouny, M; Gallinghouse, G J; Horton, R; Al-Ahmad, A; Di Biase, L; Burkhardt, J D; et al.
Abstract: Introduction: We investigated the ablation success of scar homogenization with combined (epicardial + endocardial) versus endocardial-only approach for ventricular tachycardia (VT) in patients with ischemic cardiomyopathy (ICM) at 5 years of follow-up. Method: Consecutive ICM patients undergoing VT ablation at our center were classified into group 1: endocardial scar homogenization and group 2: endocardial +epicardial scar homogenization. Patients with previous open heart surgery were excluded. All patients underwent bipolar substrate mapping with standard scar settings defined as normal tissue >1.5 mV and severe scar <0.5 mV. Non-inducibility of monomorphic VT was the procedural endpoint in both groups. Patients were followed up twice a year for 5 years with implantable device interrogations. Results: A total of 361 (Group 1: 291 and group 2: 70) patients were included in the study (mean age: 67 years, male: 88.4%). At 5 years, significantly higher number of patients from group 2 remained arrhythmia-free (figure 1). Of those patients, 87 (45%) and 51 (89%) from group 1 and 2 respectively were off-anti-arrhythmic drugs (AAD) (p<0.001). After adjusting for age, gender, hypertension, diabetes, and obstructive sleep apnea, scar homogenization using endo-epicardial approach was associated with 51% less recurrence compared to the endocardial ablation strategy (Hazard Ratio: 0.49, 95% CI: 0.27–0.89, p: 0.02). Conclusion: In this series of patients with ischemic cardiomyopathy and VT, endo-epicardial scar homogenization was associated with a lower need for AAD and a significantly lower recurrence rate at 5-years of follow-up compared to the endocardial ablation alone. Funding Acknowledgement: Type of funding sources: None.